2023
DOI: 10.1002/suco.202300239
|View full text |Cite
|
Sign up to set email alerts
|

New damage evolution law in plastic damage models for fiber‐reinforced cementitious composites

Edmir José dos Santos Júnior,
Pablo Augusto Krahl,
Francisco Alex Correia Monteiro
et al.

Abstract: Nowadays, fiber‐reinforced cement‐based composites (FRCC) can develop ductile behavior with high toughness when the matrix, fibers, and interface are optimally designed. These materials are promising solutions for constructing more resilient structures. In this context, the widespread use in large‐scale applications requires reliable models to predict the performance of FRCC structures. Usually, the studies on numerical modeling of FRCC apply the damage laws developed for quasi‐brittle concrete, making damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…Fibers are typically added to concrete to improve its properties. 6,[18][19][20] Indeed, as compared to unreinforced concrete, fiber-reinforced concrete is characterized by improved resistance to cracking, tensile strength, flexural strength, shear strength, ductility, and toughness. 21 Furthermore, adding fiber to RAC can not only improve the crack resistance, impact resistance, and ductility of concrete but also make up for some defects of RCA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fibers are typically added to concrete to improve its properties. 6,[18][19][20] Indeed, as compared to unreinforced concrete, fiber-reinforced concrete is characterized by improved resistance to cracking, tensile strength, flexural strength, shear strength, ductility, and toughness. 21 Furthermore, adding fiber to RAC can not only improve the crack resistance, impact resistance, and ductility of concrete but also make up for some defects of RCA.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the existing literature, it is found that PP fiber additions in concrete do not significantly change the compressive strength, 20,27 but these induce notably improved splitting tensile and flexural strengths. 20,25,27 More importantly, some researchers found that the drops in splitting tensile strength and flexural strength due to the substitution of NCA with RCA were to a large extent compensated by the addition of PP fibers. However, concrete in practical engineering, such as corbels, highways, bearing padding stones, and deep beams, is usually subjected to combined compression-shear loads during service.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation